Multiglandular Parathyroid Disease - Grzegorz Kowalski; Grzegorz Buła; Adam Bednarczyk; Agata Gawrychowska; Jacek Gawrychowski (Life, 2022)
Introduction: Multiglandular parathyroid disease (MGD) is an uncommon cause of primary hyperparathyroidism (pHPT) and has been reported in the literature in 8–33% of patients with pHPT. The aim of our study was to review the clinical characteristics and management of MGD and evaluation of surgical treatment failures. Methods: We performed a retrospective study of 163 patients with pHPT undergoing parathyroidectomy (PTX) at the Department of General and Endocrine Surgery between 1983 and 2018. All these patients were diagnosed with MGD. This group of patients was compared with a group of 856 patients with solitary disease operated for pHPT in the same period. Results: Among 163 patients—127 (79%) of them had two lesions, 28 (16%) had three, and 8 (5%) four. They were prevalently women over the age of 50. The diagnosis was based on PTH and ionized calcium studies and used sestamibi technetium-99m scintigraphy (MIBI) as well for us. Treatment was surgical. Conclusions: Parathyroidectomy (PTX) for multiglandular parathyroid disease (MGD) is associated with a higher operative risk of failure compared to solitary disease. Preoperative diagnosis and localization of the parathyroid glands is an extremely important element of treatment. Diagnosis is based on PTH and calcium levels. Ultrasonography (USG), MRI, and scintigraphy are very helpful in diagnosis. Mediastinal multiglandular parathyroid disease (MGD) is associated with increased surgical treatment failures. The treatment is surgical and consists of the removal of the masses or complete parathyroidectomy. Based on this study, we support the existence of multiple adenomas and advocate the removal of only macroscopically enlarged parathyroid glands in patients with primary hyperparathyroidism.